ANALISIS MISKONSEPSI BUKU TEKS BIOLOGI SMA KELAS X MATERI EUBACTERIA DI KOTA KISARAN - Riah Irawati Sihombing; Abdul Hakim Daulae; Dian Komala Sari; Hotmaria Sihotang (Jurnal Pelita Pendidikan, 2017)
This study aims to know if there were misconceptions or not in biology textbooks and the percentage ofeach category misconception of eubacteria in biology textbook for grade X senior high school based on curriculum2013 in Kisaran. This research is a qualitative descriptive research with content analysis approach. Textbooks whichanalyzed are biology textbooks for senior high school curriculum 2013 and used in Kisaran by using saturatedsampling technique. Identification of the misconception are divided into 5 categories namely undergeneralization,obsolete concept and terms, oversimplification, overgeneralization, and misidentification. The data obtaineddescriptively by calculating the frequency of each category. The results showed that misconceptions that was foundin the textbooks A and B. Misconceptions categories at the textbooks found out obsolete concept and terms,overgeneralization, and misidentification. In the textbook A was found on eubacteria.The percentage ofmisconception categories in textbook A on eubacteria was obsolote concept and terms 100%. In the textbook Bwas found on eubacteria. The percentage of misconception category in textbook B on eubacteria was obsoleteconcept and terms 33,33%, overgeneralization 33,33%, and misidentification 33,33%.Keywords: Misconception, Textbook, Eubacteria, Curriculum 2013